Therapeutic Effects of Traditional Chinese Medicine on Cardiovascular Diseases: the Central Role of Calcium Signaling - Li, Yuxin; Zhang, Zhang; Li, Sen; Yu, Tingting; Jia, Zhaoqi (Frontiers in Pharmacology, 2021)
Calcium, as a second messenger, plays an important role in the pathogenesis of cardiovascular diseases (CVDs). The malfunction of calcium signaling in endothelial cells and vascular smooth muscle cells promotes hypertension. In cardiomyocytes, calcium overload induces apoptosis, leading to myocardial infarction and arrhythmias. Moreover, the calcium–calcineurin–nuclear factor of activated T cells (NFAT) pathway is essential for expressing the cardiac pro-hypertrophic gene. Heart failure is also characterized by reduced calcium transient amplitude and enhanced sarcoplasmic reticulum (SR) calcium leakage. Traditional Chinese medicine (TCM) has been used to treat CVDs for thousands of years in China. Because of its multicomponent and multitarget characteristics, TCM's unique advantages in CVD treatment are closely related to the modulation of multiple calcium handling proteins and calcium signaling pathways in different types of cells involved in distinct CVDs. Thus, we systematically review the diverse mechanisms of TCM in regulating calcium pathways to treat various types of CVDs, ranging from hypertrophic cardiomyopathy to diabetic heart disease.